A STUDY OF EFFICACY AND SAFETY OF DRUGS USED FOR INFERTILITY AT A TERTIARY CARE CENTER-A PROSPECTIVE OBSERVATIONAL STUDY - K., SWETHA; PAWASKAR, NARESH T.; C., AMRUTA; M. R., MANASA (International Journal of Pharmacy and Pharmaceutical Sciences, 2025)
Objective: To assess the efficacy and safety of drugs used for infertility with respect to ovulation induction and conception. Methods: A prospective observational study was conducted in gynaecology Out Patient Department (OPD) of a tertiary care hospital from June 2019 to November 2019. 45 women who presented with history of infertility were included. Details of socio-demographic factors, treatment, investigations, efficacy and safety parameters were collected. Efficacy parameters considered were mature follicle ≥18 mm, endometrial thickness of ≥7 mm, occurrence of ovulation and pregnancy. Safety parameters included any adverse effects encountered during drug therapy. Results: Out of 45 patients, 24 were treated with Clomiphene citrate and 21 with Letrozole. The two groups had similar baseline characteristics. Mature follicular size was attained in 83.3% of Clomiphene citrate group and 61.9% of letrozole group. Mean endometrial thickness was 7.6 mm in Clomiphene citrate while 8.3 mm in letrozole group. Ovulation occurred in 45.8% of patients in Clomiphene citrate group and 47.6% of letrozole group. 41.7% of patients in Clomiphene citrate group and 28.6% of letrozole group conceived. However, there was no significant difference between the two groups in the above parameters. No serious adverse effects were observed. Conclusion: Both letrozole and clomiphene citrate were equally efficacious in ovulation induction and did not cause any serious adverse effects.